Dye sensitized solar cell with P(VdF-co-HFP) gel electrolyte - Kim, JY; Chung, IJ; Kim, YC; Kim, JK; Yu, JW (TAYLOR & FRANCIS LTD, 2004)
A solid-state solar cell was fabricated with acid-sensitized nanostructural tin oxide electrode and poly(oinylidene fluoride-co-hexafluropropylene)-based gel electrolyte. The effect of ionic conductivity on the device performance was investigated by varying the weight ratio of propylene carbonate acting as a plasticizer in the gel. polymer electrolyle (GPE). At a proper composition of GPE, a short circuit photocurrent density of 2.5 mA/cm(2), an open circuit photo-voltage of 0.28 V, and a fill factor of 0.51 were obtained under illumination of while Xe light with an intensity of 100 mW/cm(2).
Keywords: SOLID-STATE; DEVICES